Chronic Disease: The Epidemic of the Twentieth Century - Mills, Dora (Maine Policy Review, 2000)
One hundred years ago, the leading causes of death were infectious diseases such as tuberculosis, influenza and pneumonia. Of equal concern were water-borne diseases such as cholera and typhoid. Yet today, as a result of public health measures to clean up drinking water and provide immunizations, and by improvements in medical care, such diseases have been eradicated. As Dora Anne Mills points out, as we begin a new century, we have much to celebrate but still more to consider. Today, we face an epidemic unlike any found in 1900. One hundred years ago only one-in-six people died of a chronic condition; today, three-quarters of Maine people die from four chronic, and mostly preventable, diseases: cardiovascular disease, cancer, chronic lung disease, and diabetes. Not only does Maine have the fourth highest death rate due to chronic disease, it also leads the nation in the three behavioral risk factors that cause or exacerbate chronic disease: tobacco use, poor nutrition, and physical inactivity. In this article, Mills first chronicles Maine’s chronic disease epidemic, and second, lays out a plan for strengthening the state’s disease prevention and health promotion efforts. She calls for a local as well as a statewide focus, and suggests that efforts to change Maine’s health status will require whole communities to take coordinated action.
Keywords: Maine chronic diseases; Maine public health